The low‐abundance transcriptome reveals novel biomarkers, specific intracellular pathways and targetable genes associated with advanced gastric cancer. Issue 4 (29th August 2013) - Bizama, Carolina; Benavente, Felipe; Salvatierra, Edgardo; Gutiérrez‐Moraga, Ana; Espinoza, Jaime A.; Fernández, Elmer A.; Roa, Iván; Mazzolini, Guillermo; Sagredo, Eduardo A.; Gidekel, Manuel; Podhajcer, Osvaldo L.
<x xml:space="preserve">Abstract</x> Studies on the low‐abundance transcriptome are of paramount importance for identifying the intimate mechanisms of tumor progression that can lead to novel therapies. The aim of the present study was to identify novel markers and targetable genes and pathways in advanced human gastric cancer through analyses of the low‐abundance transcriptome. The procedure involved an initial subtractive hybridization step, followed by global gene expression analysis using microarrays. We observed profound differences, both at the single gene and gene ontology levels, between the low‐abundance transcriptome and the whole transcriptome. Analysis of the low‐abundance transcriptome led to the identification and validation by tissue microarrays of novel biomarkers, such as LAMA3 and TTN; moreover, we identified cancer type‐specific intracellular pathways and targetable genes, such as IRS2, IL17, IFNγ, VEGF‐C, WISP1, FZD5 and CTBP1 that were not detectable by whole transcriptome analyses. We also demonstrated that knocking down the expression of CTBP1 sensitized gastric cancer cells to mainstay chemotherapeutic drugs. We conclude that the analysis of the low‐abundance transcriptome provides useful insights into the molecular basis and treatment of cancer.